PERANAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU - Sunarni; Nur Khalis; Achmad (UNISAN JURNAL, 2023)
This study aims to provide an overview of the role of the principal in improving teacher performance at SMP IT Khanzanah Palembang which is explained in depth, procedures and concrete steps. This research is a form of field research. The results of the research show that the role of the Principal of SMP IT Khanzanah Palembang in carrying out their duties with full responsibility, with the aim of improving teacher performance, by taking a normative approach or motivating teachers to always work according to their duties, with expertise in the field studies that are taught, the procedure desired by the Principal in improving Teacher Performance is to carry out supervision with deliberation, communication, planning, coordination and evaluation approaches, with this implementation ultimately all purposes will be realized. Based on the research results, it can be described that to support all the Principal's programs in improving performance are external and internal factors, facilities and infrastructure, methods and programs. This research has implications that being a school leader should carry out their duties in a transparent and responsible manner, all policies taken must be transparent to their subordinates. The Principal should always consult with his subordinates once a month to carry out an evaluation. To overcome the inhibiting factors for the implementation of education, especially the success of the Principal in improving Teacher Performance, it is hoped that unity of steps and common goals of all components of the school, both the Principal, teachers, students, and parents and the surrounding community, will jointly carry out the vision and mission in The Role of the Principal in Improving Teacher Performance at SMP IT Khanzanah Palembang.